LOGIKA BERBAHASA SEBAGAI PENDETEKSI POLA PEMBERITAAN ‘NONFAKTIF’ PADA PENULISAN HEADLINE SURAT KABAR - Dinari Oktaria; Budhi Setiawan; Sumarwati Sumarwati (Jurnal Membaca Bahasa dan Sastra Indonesia, 2018)
This research is motivated by the interest to know the use of language logic in printed mass media and in Solo. The selection of print media in this research is based on the rampant cases of errors that cause mistakes in the delivery of meaning or ambiguity. This research uses critical discourse analysis method. The study used data with the technique of noting. The findings indicate negative analytic opinions already exist that are being synthesized which lead to the impression of bad news. This certainly raises people’s anxiety about events that occur. The use of diction that does not match the hyperbolic size regardless of fact. The principle principle of attention to arousing may be used originally with wise use. Can be able to good communication relationship between society and government.